Perforation stability - physical and numerical modelling - Samsuri, Ariffin; Somerville, J. M. (1991)
This paper presents the results of a study into the mechanical stability of wellbore perforations. Numerical and physical models of the main factors associated with a borehole and perforations were generated and subjected to various load regimes. The results show the effects of the main parameters on the overall stability of the structure and the implications to productivity.